Zambia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper analyzes sources of growth in Zambia. It assesses domestic debt dynamics and expenditure composition under two scenarios: first, the execution of the fiscal adjustment envisaged in the 2004 budget and in the medium-term framework; and second, the continuation of recent trends. The paper assesses movements in the external value of the kwacha using a number of different approaches. It also looks at developments in the real exchange rate and in differentials in rates of return on financial assets in Zambia and key financial centers.